PENGARUH KEPUTUSAN INVESTASI DAN KEADAAN PASAR MODAL TERHADAP NILAI PERUSAHAAN YANG DIMEDIASI OLEH RISIKO PERUSAHAAN MANUFAKTUR SEKTOR ANEKA INDUSTRI YANG TERDAFTAR DI BEI PERIODE 2008-2012 - Edy Yanto; Yulia Efni; Ahmad Fauzan Fathoni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The aim of this research is to test the direct and indirect effect of investment decision and capital market condition toward firm value in mediated by risk of manufacture companies of miscellaneous industry sectors listed in Indonesian Stock Exchange period 2008-2012. The population of the research is 54 companies. The sampling technique used purposive sampling, which obtained 21 samples of firm that fitted the sample criteria by N of data as much as 105. Data analysis used descriptive analysis and path analysis. Path Analysis results, investment decision and capital market condition had a significant influence directly toward firm value. Meanwhile investment decision directly had a significant influence toward business risk while capital market condition had no significant influence toward business risk. Business risk itself had no significant influence toward firm value, it meant that business risk could not able to mediate the influence of investment decision and capital market condition toward firm value.Keywords : investment decision, capital market condition, business risk, Tobin’s Q, path analysis